Mineralisation of CO2 in wood biomass ash for cement substitution in construction products - Tripathi, Nimisha; Hills, Colin D.; Singh, Raj S.; Kyeremeh, Stephen; Hurt, Andrew (Frontiers in Sustainability, 2024)
This study extends our exploration of the potential of biomass ashes for their CO2reactivity and self-cementing properties. The ability of three hard wood-based biomass ashes to mineralise CO2 gas and partially replace CEM I in mortars was investigated. The three hard woods were English oak (Quercus rober), English lime (Tilia x europaea) and beech (Fagus sylvatica). The woody biomass wastes were incinerated at 800 °C to extract their key mineral phases, which are known to be reactive to CO2 gas to form carbonates. The selected biomass ashes were analysed for their CO2-reactivity, which was in the range of 32-43% (w/w). The ashes were used to replace CEM I at 7% and 15% w/w and this 'binder' was mixed with sand and water to produce cylindrical monolithic samples. These monoliths were then carbonated and sealed cured over 28 days. The compressive strength, density and microstructure of the carbonate-hardened monoliths were examined. The ash-containing monoliths displayed mature strengths comparable to the cement-only reference samples. The CO2 uptake of oak containing monoliths was 7.37 and 8.29% w/w, for 7 and 15% ash substitutions, respectively. For beech and English lime they were 4.96 and 6.22% w/w and 6.43 and 7.15% w/w, respectively. The 28 day unconfined compressive strengths for the oak and beech ashes were within the range of ~80-94% of the control, whereas lime ash was 107% of the latter. A microstructural examination showed carbonate cemented sand grains together highlighting that biomass ash-derived minerals can be very CO2 reactive and have potential to be used as a binder to produce carbonated construction materials. The use of biomass to energy ash-derived minerals as a cement replacement may have significant potential benefits, including direct and indirect CO2 emission savings in addition to the avoidance of landfilling of these combustion residues.